PENGARUH KEGIATAN EKSTRAKURIKULER DAN SIKAP BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI DAN XII IPS DI SMA NEGERI 8 KOTA JAMBI - Redi Indra Yudha (Universitas Batanghari Jambi, 2016)
The purpose of this research is to describe and influence of extra-curricular activities and learning attitude towards learning outcomes on economic subjects students at SMA Negeri 8 Kota Jambi. As for the sample totaled 151 students by using proportional random sampling technique. Based on the results, it can be concluded that the presence of extra-curricular activities will educate students in attitude in the learning process and improve the students' interests and talents in order to obtain the results of learning more than ever.Keyword : Extracurricular Activities, Attitudes Learning, Learning Outcomes.